H2 sensing performance of optical fiber coated with nano-platelet WO3 film - Ou, Jian Zhen; Yaacob, Mohd. Hanif; Campbell, Jos Laurie; Breedon, Michael; Kalantar-zadeh, Kourosh; Wlodarski, Wojtek (Elsevier, 2012)
For the first time, we have integrated nano-platelet Pd/WO3 films, which are formed using an acid etching method, with optical fibers to develop a hydrogen gas (H2) sensors. The tungsten films were firstly RF sputtered on top of optical fiber tips, and subsequently etched in 1.5 M nitric acid to produce tungstite films. After annealing at 300 and 480 °C, these films were coated with approximately 25 Å thick Pd layers. The films were characterized using SEM, GADDS, EDX, and both Raman and UV–vis–NIR spectroscopy. H2 testing measurements were conducted when the sensors were interacting with 0.06–1% H2 in synthetic air at an optimum temperature of 100 °C. It was found that the highly crystalline nano-platelet Pd/WO3 film based optical fiber H2 sensors show large reflectance responses in the NIR wavelength of 6% and 12% in the presence of 0.06% and 1% H2, respectively.